2018
DOI: 10.3389/fpsyg.2018.01928
|View full text |Cite
|
Sign up to set email alerts
|

Some Pieces Are Missing: Implicature Production in Children

Abstract: Until at least 4 years of age, children, unlike adults, interpret some as compatible with all. The inability to draw the pragmatic inference leading to interpret some as not all, could be taken to indicate a delay in pragmatic abilities, despite evidence of other early pragmatic skills. However, little is known about how the production of these implicature develops. We conducted a corpus study on early production and perception of the scalar term some in British English. Children's utterances containing some w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
1
10
0
5
Order By: Relevance
“…Moreover, as Eiteljoerge et al (2018) observed, the low rate of produced implicatures in a children's corpus should not come as a surprise. In fact, children's production was in line with mothers' usage, as the analysis of mothers' child-directed speech revealed.…”
Section: The Pragmatic Tolerance Accountmentioning
confidence: 68%
See 4 more Smart Citations
“…Moreover, as Eiteljoerge et al (2018) observed, the low rate of produced implicatures in a children's corpus should not come as a surprise. In fact, children's production was in line with mothers' usage, as the analysis of mothers' child-directed speech revealed.…”
Section: The Pragmatic Tolerance Accountmentioning
confidence: 68%
“…However, as we will now see, further experimental evidence (Eiteljoerge et al, 2018) casts doubt on the plausibility of the lexicalist account.…”
Section: The Lexicalist Accountmentioning
confidence: 82%
See 3 more Smart Citations